COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE BEFORE AND AFTER MERGER (CASE STUDY AT PT HOLCIM INDONESIA) - hilmi hatta, achmad setiawan; handini, sri (Ekspektra : Jurnal Bisnis dan Manajemen, 2021)
This study aims to analyze differences in the company's financial performance before & after the merger of PT Holcim Indonesia Tbk. The company's financial performance is measured using financial ratios: liquidity ratios (current ratio & cash ratio), solvency ratios (debt ratio & debt equity ratio), activity ratios (total assets turn over & fixed assets turn over), profitability ratios (nett profit margin & gross profit margin), & market ratio (earnings per share & price earnings ratio). The quantitative method used in this study takes data from PT Holcim Indonesia Tbk's financial statements for the 2014-2017 period. The analysis technique uses SPSS software. The results of the calculation of financial performance before & after showed a decrease in post-merger performance on all liquidity ratios, activity ratios, profitability ratios, & market ratios, only the solvency ratio increased. Then do a paired sample t test which concludes that there is no significant difference from the average financial performance ratio before and after the merger. This is because the difference in the ratio before and after the merger is not much different.